Advances in Management of Esophageal Motility Disorders - Tangaroonsanti, Anupong; Siramolpiwat, Sith; Mahachai, Varocha; Vilaichone, Ratha-korn (The Bangkok Medical Journal, 2017)
Esophageal manometry is an important tool for evaluating esophageal function. It can be used for assessing the esophageal peristaltic pattern and also peristaltic intensity. Additionally, lower esophageal sphincter (LES) function can be studied simultaneously. This information allows clinicians to thoroughly investigate patients presenting with esophageal and/or respiratory symptoms without identifable structural cause. At present, high resolution manometry (HRM) is preferred over conventional manometry as it informs the result in pressure topography. These data correlate more precisely with the clinical presentation of patients with esophageal dysmotility. Consequently, the HRM working group has proposed the criteria known as Chicago classifcation to categorize and specify the esophageal motility abnormality based on the results from HRM. This article describes esophageal motility disorders according to the current diagnostic criteria and also how to manage them in brief.